Twilight ; Life and death : a reimagining of the classic novel - Meyer, Stephenie, 1973- (Little, Brown and Co., 2015)
"Twilight:" Seventeen-year-old Bella leaves Phoenix to live with her father in Forks, Washington, where she meets an exquisitely handsome boy at school for whom she feels an overwhelming attraction and who she comes to realize is not wholly human.